(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2023)
This present research aims at identifying the dimensions of the psychological capital of the employees of the directorate of Education in Nineveh expressed by its dimensions:(self-efficiency, hope, optimism and flexibility). The questionnaire forms were adopted as the main tool to collect the data and the statistical software SPSS V26 and AMOS software were used to analyze the data of (202) subjects as employees in who occupy managerial level positions through several descriptive and analytical approaches. From the results of the statistical analysis, a set of conclusions were drawn, which showed the results of the field research via diagnosing the availability of the psychological capital dimensions in the field researched and this indicates that the Directorate of Education in Nineveh pay a good attention to building a psychological capital, which is represented by its dimensions that lead to the progress and advance of the individuals. Moreover, the research submitted a group of recommendations including the necessity to pay a considerable attention to the psychological capital as it is a very vital topic and as it has an important effect on the psychology of the individual who works in an organization and which can provide good benefits and a competitive advantage.